PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO - Agatha Rezkhi Dyanthika Putri; Heny Kurnianingsih (Globalwriting Academica Consulting & Publishing, 2022)
The study is aimed at identifying the quality of the product, the price and promotion of the smartphone OPPO decision. The rapid telecommunications industry, which is a reflection of the tight and high demand for information available to the public. The study is conducted on consumers who come from the town of solo. After a library review, and the drafting of hypotheses and compiled through a questionnaire's method spread to 160 people.Data processing USES SPSS 21. Then analysis using validity tests, religious tests, linear regressions, t tests, f tests, and determinations so that they have a Y = 1.517 + 0.245 + 0.309 + 0.322. Research shows that quality, price and promotion have both a positive and significant impact on purchasing decisions. The large variable of the impact of the promotion of 0.322 and the price of 0.309 and the small factor affecting the decision of purchase of 0.245.